2021
DOI: 10.1074/jbc.ra120.015679
|View full text |Cite
|
Sign up to set email alerts
|

Danish and British dementia ITM2b/BRI2 mutations reduce BRI2 protein stability and impair glutamatergic synaptic transmission

Abstract: Mutations in Integral membrane protein 2B (ITM2b/BRI2) gene causes familial British and Danish dementia (FBD and FDD), autosomal dominant disorders characterized by progressive cognitive deterioration. Two pathogenic mechanisms, which may not be mutually exclusive, have been proposed for FDD and FBD: 1) loss of BRI2 function; 2) accumulation of amyloidogenic mutant BRI2-derived peptides, but the mechanistic details remain unclear. We have previously reported a physiological role of BRI2 in excitatory synaptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…To explore early dysfunctions that may underlie initial mechanisms leading to dementia, we studied young KI rats carrying the Itm2b D Familial Danish dementia mutation. Consistent with the findings in Itm2b D/D mouse KIs (41), we found that Bri2-ADan maturation is altered and accumulates in Itm2b D/D primary neurons (Figure 2). Analysis of APP metabolism in peri-adolescent Itm2b D Ki rats (Figure 3 and 4) only showed subtle but significant changes in Aβ42 and Aβ43 steady-state levels, which were slightly increased and decreased, respectively (Figure 3).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…To explore early dysfunctions that may underlie initial mechanisms leading to dementia, we studied young KI rats carrying the Itm2b D Familial Danish dementia mutation. Consistent with the findings in Itm2b D/D mouse KIs (41), we found that Bri2-ADan maturation is altered and accumulates in Itm2b D/D primary neurons (Figure 2). Analysis of APP metabolism in peri-adolescent Itm2b D Ki rats (Figure 3 and 4) only showed subtle but significant changes in Aβ42 and Aβ43 steady-state levels, which were slightly increased and decreased, respectively (Figure 3).…”
Section: Discussionsupporting
confidence: 91%
“…Bri2 modulates glutamatergic synaptic transmission at both pre- and post-synaptic termini of Schaeffer-collateral pathway (SC)-CA3>CA1 synapses (47). This function is compromised in both adult Itm2b D and Itm2b B KI mice (41). Here, analyzed glutamatergic transmission at SC-CA3>CA1 synapses in young peri-adolescent Itm2b D male and female rats.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even more interesting is tea extract can block the reduction of TH, an enzyme that catalyzes tyrosine to L-dihydroxyphenylalanine (L-DOPA) in the dopamine biosynthesis pathway, finally preventing the death of dopaminergic neurons [ 125 ]. It is known that Glutamic acid (Glu) is one of the most important endogenous excitatory neurotransmitters; its excessive release will produce neurotoxicity, which is closely related to dementia, depression, and other diseases [ 126 ]. In the organotypic culture of the motor neuronal spinal cord in rats, EGCG was observed to block the Glu excitotoxicity induced by threonine-hydroxyapatite (THA) and regulate the level of Glu in cells.…”
Section: Mechanisms Of the Neuroprotective Effect Of Tpsmentioning
confidence: 99%